Hybrid Warfare and Customs Security: Strengthening Resilience for Sustainable Development - Lomachinska Іrіna; Ishchuk, Mykhailo; Chornomordenko, Ivan; Taran, Ganna; Turchyn, Maryna; Martsinko, Natalia; Pasko, Kateryna; Lobanchuk, Olena (European Journal of Sustainable Development, 2025)
This article examines the threats facing Ukraine’s customs system in the context of hybrid warfare waged by the Russian Federation in the digital era. It explores key scientific approaches to defining the concept of “hybrid warfare”, which is characterized as a complex, multidimensional phenomenon that integrates military, informational, cyber, economic, and political instruments of influence. This form of aggression complicates the identification, counteraction, and neutralization processes, while simultaneously posing a threat to critical components of national resilience. The article emphasizes that hybrid warfare targets the disruption of essential infrastructure, including law enforcement agencies, healthcare systems, food security, transportation networks, the economy, and other sectors vital to the functioning of the state. Particular attention is given to the indirect influence tools employed by the aggressor state, such as support for separatist and terrorist groups, which may involve financing, arming, and carrying out acts of state terrorism. The article also highlights the impact of informational and psychological campaigns designed to transform public opinion destructively in the targeted countries. In the case of Ukraine’s customs service, it outlines the diverse methods of hybrid influence, including economic pressure through customs mechanisms, the creation of artificial trade barriers, the spread of contraband, cyberattacks on customs infrastructure, campaigns to discredit customs authorities, the use of corruption schemes, and political-legal manipulations aimed at delaying reforms and influencing foreign economic agreements. The article concludes that customs security has become a priority not only for national security but also as an essential element in achieving the United Nations’ Sustainable Development Goals related to peace, justice, institutional resilience, and economic stability. The article underscores the need for the digital transformation of Ukraine’s customs system as a strategic response to modern challenges. Such transformation will help strengthen institutional resilience, enhance public trust, ensure procedural transparency, and improve Ukraine’s position in the global information space. Keywords: hybrid warfare, customs security, digital transformation, cyber threats, institutional resilience, information security, sustainable development goals, economic stability